1992
DOI: 10.1017/s0022149x00012724
|View full text |Cite
|
Sign up to set email alerts
|

In vivo passage through calves of nematophagous fungi selected for biocontrol of parasitic nematodes

Abstract: The experiment was designed to test the survival and performance of stress selected nematophagous fungi after passage through the gastro-intestinal tract of cattle. Ruminating calves were fed daily with a fixed amount of fungal material grown on barley grains. The excreted dung was collected on days four and five after the start of the feeding experiment. Barley grains were washed out of the excreted dung and incoculated on water-agar plates. After incubation for one week, nine out of ten fungal isolates were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
2
2

Year Published

1995
1995
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(35 citation statements)
references
References 7 publications
1
30
2
2
Order By: Relevance
“…Inoculation of these organisms into a sodium alginate matrix, to form pellets, is a more recent method that has presented good results (LARSEN, 1992;ARAÚJO et al, 2004a;DIAS et al, 2007;TAVELA et al, 2011). On the other hand, there has been much discussion on the use of different isolates of the same species of fungus under the same conditions, in this case partly natural, which could present distinct results.…”
Section: Discussionmentioning
confidence: 99%
“…Inoculation of these organisms into a sodium alginate matrix, to form pellets, is a more recent method that has presented good results (LARSEN, 1992;ARAÚJO et al, 2004a;DIAS et al, 2007;TAVELA et al, 2011). On the other hand, there has been much discussion on the use of different isolates of the same species of fungus under the same conditions, in this case partly natural, which could present distinct results.…”
Section: Discussionmentioning
confidence: 99%
“…Duddingtonia flagrans é um fungo que possui grande capacidade de produzir clamidósporos, que permanecem viáveis depois de ingeridos e eliminados pelas fezes, colonizando-as logo após a sua deposição no solo e predando os nematódeos por meio de hifas adesivas (LARSEN et al, 1992;WAGHORN et al, 2003). Devido a sua forma de ação, o uso do fungo D. flagrans tem atraído muita atenção e tem sido foco de inúmeras pesquisas na última década (NANSEN et al, 1995;FERNÁNDEZ et al, 1999;SARKUNAS et al, 2000;FAEDO et al, 2002;DIMANDER et al, 2003a;DIMANDER et al 2003b;EYSKER et al, 2005).…”
Section: Marta Bañolasunclassified
“…To date, most of the successful field trials have been done used a single Danish 'super-isolate ' selected for its ability to survive passage through the gastro-intestinal tract of cattle (Larsen et al 1992). The low level of genetic variation and the lack of geographical differentiation should be considered in future screening programs aiming at isolating strains of D. flagrans with an improved capacity to control parasitic nematodes.…”
Section: Discussionmentioning
confidence: 99%
“…One of the most promising candidates for study was the net-forming nematodetrapping Duddingtonia flagrans. In 1992, a strain of D. flagrans was isolated in Denmark, whose spores (chlamydospores) survived passage through the gastrointestinal tract of cattle (Larsen et al 1992). Subsequently, trials all over the world have demonstrated that the feeding of D. flagrans spores to grazing animals results in successful suppression of the numbers of parasitic nematodes on pasture, and hence diminishes the parasitic burden on various hosts (Faedo et al 1998, Larsen 1999, Knox, Josh & Anderson 2002, Waller 2003.…”
Section: Introductionmentioning
confidence: 99%